Phylosymbiosis and metabolomics resolve phenotypically plastic and cryptic sponge species in the genus Agelas across the Caribbean basin - M. S. Pankey; D. J. Gochfeld; M. Gastaldi; K. J. Macartney; A. Clayshulte Abraham; M. Slattery; M. P. Lesser (Molecular Ecology, 2024)
Fundamental to holobiont biology is recognising how variation in microbial composition and function relates to host phenotypic variation. Sponges often exhibit considerable phenotypic plasticity and also harbour dense microbial communities that function to protect and nourish hosts. One of the most prominent sponge genera on Caribbean coral reefs is Agelas . Using a comprehensive set of morphological (growth form, spicule), chemical and molecular data on 13 recognised species of Agelas in the Caribbean basin, we were able to define only five species (=clades) and found that many morphospecies designations were incongruent with phylogenomic and population genetic analyses. Microbial communities were also strongly differentiated between phylogenetic species, showing little evidence of cryptic divergence and relatively low correlation with morphospecies assignment. Metagenomic analyses also showed strong correspondence to phylogenetic species, and to a lesser extent, geographical and morphological characters. Surprisingly, the variation in secondary metabolites produced by sponge holobionts was explained by geography and morphospecies assignment, in addition to phylogenetic species, and covaried significantly with a subset of microbial symbionts. Spicule characteristics were highly plastic, under greater impact from geographical location than phylogeny. Our results suggest that while phenotypic plasticity is rampant in Agelas , morphological differences within phylogenetic species affect functionally important ecological traits, including the composition of the symbiotic microbial communities and metabolomic profiles.